The Effect of PowerPoint-Based Card-Assisted TGT Cooperative Learning Model on Chemical Bonding Material on Student Learning Outcomes - Hizratul Fitria; Herlinawati Herlinawati (UNDIKMA, 2023)
This study aims to determine the effect of the TGT-type cooperative learning model assisted by PowerPoint-based cards on chemical bonding material on student learning outcomes. This type of research is a type of experimental research with a quantitative approach. The population in this study were all students of class X MIPA at SMA Negeri 15 Medan. Samples were taken by purposive sampling of 2 classes. The treatment of the two sample classes was distinguished by the use of the TGT learning model in the experimental class while the control class used the conventional learning model with the same media. The instrument used was a multiple choice test instrument with 20 questions. Data were analyzed by normality, homogeneity, and two-party hypothesis testing with a significance level of 0.05. the results of the data analysis show that: There is an influence of the PowerPoint-based card-assisted TGT type cooperative learning model on student learning outcomes in chemical bonding material where the average value of students taught with PowerPoint-based card-assisted TGT type cooperative learning model on student learning outcomes in bonding material chemistry was significantly higher at 81.11 in the experimental class than the average value of students who were taught with conventional PowerPoint-based card-assisted learning models on student learning outcomes in chemical bonding material of 73.75 in the control class.